1994
DOI: 10.1002/j.1460-2075.1994.tb06612.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic lethality with fibrillarin identifies NOP77p, a nucleolar protein required for pre-rRNA processing and modification.

Abstract: The nucleolar protein fibrillarin (encoded by the NOP1 gene in yeast), is required for many post‐transcriptional steps in yeast ribosome synthesis. A screen for mutations showing synthetic lethality with a temperature sensitive nop1‐5 allele led to the identification of the NOP77 gene. NOP77 is essential for viability and encodes a nucleolar protein with a predicted molecular weight of 77 kDa. Depletion of NOP77p impairs both the processing and methylation of the pre‐rRNA. The processing defect is greatest for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
109
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 55 publications
14
109
0
Order By: Relevance
“…The results presented in this study, however, support a model where Dbp9p would act at a very early step in the formation of 60S ribosomal subunits+ First, the most pronounced pre-rRNA processing phenotype associated with the genetic depletion of Dbp9p is the reduced formation and the lower steady-state levels of all 27S precursors, especially of the 27SB pre-rRNAs, to mature 25S and 5+8S rRNA+ Similar phenotypes have been observed upon depletion of other protein trans-acting factors (Bergès et al+, 1994;Sun & Woolford, 1994;Kressler et al+, 1998;Zanchin & Goldfarb, 1999), and they are most readily explained by the instability of early pre-ribosomal particles (discussed in Kressler et al+, 1999b)+ Second, Dbp9p depletion affects 18S rRNA production more drastically than depletion of other protein trans-acting factors involved in 60S-ribosomalsubunit biogenesis does (Bergès et al+, 1994;Sun & Woolford, 1994;de la Cruz et al+, 1998;Kressler et al+, 1999c;Zanchin & Goldfarb, 1999;Burger et al+, 2000)+ Intriguingly, the block of the early cleavages at sites A 0 to A 2 , however, seems to be less pronounced, as judged by the relatively low levels of 23S rRNA accumulation, upon Dbp9p depletion+ One conceivable explanation is that the instability of early pre-ribosomal particles is masking the effect of inhibited A 0 to A 2 cleavage; delayed or blocked cleavage at these sites is generally observed in mutants affecting 60S-ribosomal-subunit biogenesis (discussed in Venema & Tollervey, 1999)+ Finally, our genetic data (synthetic lethality, dosage suppression, and weak interaction in a yeast two-hybrid assay) indicate that Dbp9p functionally interacts with Dbp6p, which has been previously suggested to be acting at an early step on the pathway to formation of 60S ribosomal subunits (Kressler et al+, 1998(Kressler et al+, , 1999a)+ The observed genetic interactions are highly specific because neither the dbp9 nor dbp6 mutant phenotypes are synthetically enhanced by, for example, the spb4-1 mutation (data not shown and Kressler et al+, 1999a)+ Moreover, the cold sensitivity of the dbp6-4 mutant cannot be suppressed by overexpression of other DEADbox proteins, such as Dbp10p and Spb4p, implicated in the biogenesis of 60S ribosomal subunits (data not shown)+ Interestingly, this is the first time that a putative RNA helicase has been shown to suppress a mutation in another helicase gene involved in ribosome biogenesis+ A similar suppression has so far only been demonstrated for the cytoplasmic Ded1p by its homolog Dbp1p (Jamieson & Beggs, 1991)+ However, in this case, overexpression of Dbp1p results in a bypass suppression, which is clearly not the case for the couple DBP6/DBP9+ Increased dosage of Dbp9p allows suppression of certain dbp6 mutant alleles indicati...…”
Section: Discussionsupporting
confidence: 78%
“…The results presented in this study, however, support a model where Dbp9p would act at a very early step in the formation of 60S ribosomal subunits+ First, the most pronounced pre-rRNA processing phenotype associated with the genetic depletion of Dbp9p is the reduced formation and the lower steady-state levels of all 27S precursors, especially of the 27SB pre-rRNAs, to mature 25S and 5+8S rRNA+ Similar phenotypes have been observed upon depletion of other protein trans-acting factors (Bergès et al+, 1994;Sun & Woolford, 1994;Kressler et al+, 1998;Zanchin & Goldfarb, 1999), and they are most readily explained by the instability of early pre-ribosomal particles (discussed in Kressler et al+, 1999b)+ Second, Dbp9p depletion affects 18S rRNA production more drastically than depletion of other protein trans-acting factors involved in 60S-ribosomalsubunit biogenesis does (Bergès et al+, 1994;Sun & Woolford, 1994;de la Cruz et al+, 1998;Kressler et al+, 1999c;Zanchin & Goldfarb, 1999;Burger et al+, 2000)+ Intriguingly, the block of the early cleavages at sites A 0 to A 2 , however, seems to be less pronounced, as judged by the relatively low levels of 23S rRNA accumulation, upon Dbp9p depletion+ One conceivable explanation is that the instability of early pre-ribosomal particles is masking the effect of inhibited A 0 to A 2 cleavage; delayed or blocked cleavage at these sites is generally observed in mutants affecting 60S-ribosomal-subunit biogenesis (discussed in Venema & Tollervey, 1999)+ Finally, our genetic data (synthetic lethality, dosage suppression, and weak interaction in a yeast two-hybrid assay) indicate that Dbp9p functionally interacts with Dbp6p, which has been previously suggested to be acting at an early step on the pathway to formation of 60S ribosomal subunits (Kressler et al+, 1998(Kressler et al+, , 1999a)+ The observed genetic interactions are highly specific because neither the dbp9 nor dbp6 mutant phenotypes are synthetically enhanced by, for example, the spb4-1 mutation (data not shown and Kressler et al+, 1999a)+ Moreover, the cold sensitivity of the dbp6-4 mutant cannot be suppressed by overexpression of other DEADbox proteins, such as Dbp10p and Spb4p, implicated in the biogenesis of 60S ribosomal subunits (data not shown)+ Interestingly, this is the first time that a putative RNA helicase has been shown to suppress a mutation in another helicase gene involved in ribosome biogenesis+ A similar suppression has so far only been demonstrated for the cytoplasmic Ded1p by its homolog Dbp1p (Jamieson & Beggs, 1991)+ However, in this case, overexpression of Dbp1p results in a bypass suppression, which is clearly not the case for the couple DBP6/DBP9+ Increased dosage of Dbp9p allows suppression of certain dbp6 mutant alleles indicati...…”
Section: Discussionsupporting
confidence: 78%
“…We report the analysis of pre-rRNA processing in strains lacking Rnt1p+ Cleavage in the 39 ETS was found to be blocked in the rnt1-⌬ strain, as previously reported for the rnt1-1 strain (Abou Elela et al+, 1996), leading to the synthesis of 39 extended forms of the pre-rRNAs and 25S rRNA+ In contrast, the three early pre-rRNA cleavages at sites A 0 , A 1 , and A 2 were not blocked in the absence of Rnt1p, although they were delayed, leading to accumulation of the 35S* pre-rRNA+ It is notable that many mutants defective in the synthesis of the 60S ribosomal subunit show defects in the early pre-rRNA processing steps that are similar to those observed in the rnt1-⌬ strains (see, for example, Bergès et al+, 1994;Weaver et al+, 1997;Zanchin et al+, 1997;Daugeron & Linder, 1998;de la Cruz et al+, 1998ade la Cruz et al+, , 1998bKressler et al+, 1998)+ All of these mutations are characterized by underaccumulation of the 5+8S and 25S rRNAs and 60S ribosomal subunits+ Cleavage at sites A 0 , A 1 , and A 2 is inhibited, with accumulation of the 35S pre-rRNA, appearance of the 23S rRNA, and reduced levels of the 20S pre-rRNA+ This is not, however, accompanied by reduced synthesis of mature 18S rRNA, showing that the early cleavages are delayed rather than being blocked+ In cells lacking Rnt1p, defective processing in the 39 ETS may result in misassembly of the 60S ribosomal subunits+…”
Section: Discussionmentioning
confidence: 96%
“…In many characterized mutants that are defective in synthesis of the 60S subunits, most r-proteins and the 27S pre-rRNAs are degraded rapidly+ This is seen on depletion of some 60S subunit r-proteins, e+g+, L16 (Moritz et al+, 1990), or with mutations in trans-acting factors that are believed to function at early steps in the 60S ribosomal subunit assembly pathway, e+g+, Nop4p/ Nop77p, Dbp6p or Dbp7p (Bergès et al+, 1994;Sun & Woolford, 1994;Daugeron & Linder, 1998;Kressler et al+, 1998)+ In contrast, the accumulation of the 27SB pre-rRNAs observed in the spb4-1 and GAL::SPB4 strains most resembles the phenotypes described for strains depleted of Nop2p, Nop3p, or Nip7p (Russell & Tollervey, 1992;Hong et al+, 1997;Zanchin et al+, 1997)+ We speculate that Spb4p, as well as Nop2p, Nop3p, and Nip7p, are required for a late step in the 60S ribo-FIGURE 9. HA-Spb4p localizes to the nucleolus+ Indirect immunofluorescence was performed with cells expressing HASpb4p from the SPB4 promoter (JDY8-1A YCplac111-HA-SPB4)+ A: Nop1p was detected by polyclonal rabbit anti-Nop1p antibodies, followed by decoration with a goat anti-rabbit fluorescein-conjugated antibody+ B: HA-Spb4p was detected by the monoclonal mouse anti-HA 16B12 antibody, followed by decoration with a goat anti-mouse rhodamine-conjugated antibody+ C: Chromatin DNA was stained using 49,6-diamidino-2-phenylindole dihydrochloride (DAPI)+ Pseudo-colors were assigned to the digitized micrographs (A-C) and images were merged+ Overlapping distributions are revealed in: (D) yellow for Nop1p and HA-Spb4p colocalization; (E) magenta for HA-Spb4p and chromatin DNA colocalization; and (F) cyan for Nop1p and chromatin DNA colocalization+ somal subunit assembly+ In the absence of the activity of these factors, the pre-ribosomes accumulate in a form that is relatively close to the normal structure, leading to their co-sedimentation with the normal 66S pre-ribosomes+ Some structural defects, however, prevent the processing reactions at sites C 1 and C 2 from proceeding, preventing synthesis of the 25S and 5+8S rRNAs+ In view of the presumed ATP-dependent RNA helicase activity of Spb4p, we assume that it normally functions in the restructuring of the pre-rRNA within the 66S pre-ribosome+ Ten putative ATP-dependent RNA helicases have been reported to function in ribosome biogenesis (see Introduction)+ Because most of the genes are essential for viability, we conclude that each of these proteins plays a specific, nonredundant function during ribosome biogenesis+ This interpretation is supported by the fact that overexpression of other genes encoding putative RNA helicases required for the 60S ribosomal subunit synthesis (DBP6, DBP7, and DRS1) do not suppress either the slow-growth phenotype or the coldsensitivity of the spb4-1 mutant and do not bypass the lethal phenotype of the spb4 null strain (data not shown)+ In addition, overexpression of SPB4 does not suppress the slow-growth and the temperature sensitivity of dbp6 (D+ Kressler & P+ Linder, unpubl+) or dbp7 mutants (Daugeron & Linder, 1998) and double spb4-1 dbp6 or spb4-1 dbp7 mutants are not synthetically lethal (Daugeron & Linder, 1998 and data not shown)+ During th...…”
Section: Discussionmentioning
confidence: 99%